Analytical Study on the Urgency of Media Learning in Islamic Religious Education - Mayarisa, Diyah (International Journal Education and Computer Studies (IJECS), 2023)
To optimize the efficacy of learning media within Islamic religious education, educators are urged to judiciously select and seamlessly integrate media aligned with specific learning objectives and tailored to student profiles. The utilization of learning media should serve as a conduit for enriching the Islamic educational journey, fostering deeper comprehension, and cultivating an enhanced appreciation of Islamic principles. Contemporary students have been nurtured in the digital age, exhibiting a heightened familiarity with technology. Hence, the incorporation of digital learning media holds promise in rendering the exploration of the Islamic faith more pertinent and engaging. Furthermore, learning media presents an opportunity to economize time and resources, particularly by furnishing content-rich educational materials. This, in turn, alleviates the burden on educators, affording them greater latitude for direct instructional focus. The effectiveness of learning media hinges not solely upon the media type but also on its adept integration into the pedagogical framework. Relevance to the stipulated learning objectives remains paramount, with the media serving as a scaffold to bolster desired competencies, knowledge acquisition, and skill development. To kindle student interest and motivation, employing captivating imagery, videos, or narratives germane to students' experiences is instrumental. Media that facilitates interactive engagement tends to yield greater efficacy, enabling students to actively participate in learning through activities such as problem-solving, discussion, and responsive inquiries.